Detecting counterfeit brandies - Wang, Benhua; Han, Jinsong; Zhang, Hao; Bender, Markus; Seehafer, Kai; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
A hypothesis-free sensor array (optoelectronic tongue) composed of an anionic, a cationic and two neutral poly(para-aryleneethynylene)s (PAE) at pH 3, 7 and 13 discriminate more than 30 spirits (including brandy, Branntwein, Cognac, Spirituose, and Weinbrand). Counterfeits (made by mixing of low-quality spirits and caramel colour) and different batches of identical brands of brandies are discriminated. The sensor array works without sample preparation or great instrumental cost, and is superior to conventional methods with respect to sample need (10-20 μL), time and effort. The discrimination stems from differential fluorescence quenching of the PAE-array by the complex mixture of the beverages’ colourants, from the oak barrels or added caramel colour. The collected quenching data were analysed by linear discriminant analysis (LDA) and principal component analysis (PCA) to achieve successful discrimination.
Gesehen am 06.05.2019